Intravascular Lithotripsy for Calcium Modification in Chronic Total Occlusion Percutaneous Coronary Intervention. (21st June 2021) - Øksnes, Anja; Cosgrove, Claudia; Walsh, Simon; Løland, Kjetil Halvorsen; Laffan, Jack; Biswas, Sinjini; Shaukat, Aadil; Hanratty, Colm; Strange, Julian; Spratt, James C. S.; McEntegart, Margaret
Abstract : Intravascular lithotripsy (IVL) has been shown to be safe and effective for calcium modification in nonocclusive coronary artery disease (CAD), but there are only case reports of its use in calcified chronic total occlusions (CTO). We report data from an international multicenter registry of IVL use during CTO percutaneous coronary intervention (PCI) and provide provisional data regarding its efficacy and safety. During the study period, IVL was used in 55 of 1053 (5.2%) CTO PCI procedures. IVL was used within the occluded segment after successful CTO crossing in 53 procedures and during incomplete CTO crossing in 2 cases. The mean J-CTO score was 3.1. CTO PCI technical and procedural success was achieved in 53 (96%) and 51 (93%) cases. Six patients had a procedural complication, with 3 main vessel perforations (5%). Two had covered stent implantation, one required pericardiocentesis, and one was managed conservatively. All had combination therapy with another calcium modification device. Two patients had a procedural myocardial infarction (PMI) (4%), and two others had a major adverse cardiovascular event (MACE) (4%) at a median follow-up of 13 (4–21) months. IVL can effectively facilitate calcium modification during CTO PCI. More data are required to establish the efficacy and safety of IVL and other calcium modification devices when used extraplaque or in combination during CTO PCI.